A Media Epigraphy of Video Compression - Jancovic, Marek. author. aut Link
XVI, 268 p. 44 illus., 25 illus. in color.
Keywords: "This is the book I've been waiting to read! Jancovic’s exciting method of media epigraphy draws, out of a still image, deep histories of mathematics, technologies, power, embodiment, and energy. […] An ontological struggle lodges in our squinting eyes." —Professor Laura U. Marks, Simon Fraser University "This is a must-read book for anyone looking for a model of how to successfully undertake a detailed, nuanced, and layered materialist study of even the most seemingly immaterial process." —Professor Lori Emerson, University of Colorado Boulder, Founding Director of the Media Archaeology Lab "Jancovic’s erudite tracing of that liminal threshold where visuality is just about to blur and to glitch is a magnificent take on the cultural politics of perception. […] Cultural techniques of folding and trimming link media periods from paper and books to signals and electromagnetic waves." —Professor Jussi Parikka, Aarhus University and Winchester School of Art This book explores the historical interrelationships between mathematics, medicine and media, and offers a unique perspective on how video compression has shaped our relationship with moving images and the world. It situates compression in a network of technological, visual and epistemic practices spanning from late 18th-century computational methods to the standardization of electrical infrastructure and the development of neurology throughout the 1900s. Bringing into conversation media archaeology, science and technology studies, disability studies and queer theory, each chapter offers an in-depth look at a different trace of compression, such as interlacing, macroblocking or flicker. This is a story of forgotten technologies, unusual media practices, strange images on the margins of visual culture and inventive ways of looking at the world. Readers will find illuminating discussions of the formation of complex scientific andmedical systems, and of the violent and pleasurable interactions between our bodies and media infrastructure. Marek Jancovic is Assistant Professor of Media Studies at the Vrije Universiteit Amsterdam. His research is centered around the materialities of the moving image, media and the environment, film preservation practices, and format studies.